3D Landscape Recording and Modeling of Individual Trees - Shafarina Wahyu Trisyanti; Deni Suwardhi; Agung Budi Harto (Bogor Agricultural University, Indonesia, 2019)
The 3D city/landscape model is digital representation of real environment that can be used for planner or landscape architecture in urban development planning. That model’s more focused on building, whereas vegetation model’s also needed for urban planning simulation. This research purposes are to map existing vegetation and to generate individual trees model in some level of details. The research area is campus of ITB Jatinangor and the used data are orthophoto and DSM from UAV-Photogrammetry technology. Manual segmentation, classification, and NDSM generation process can provide tree information (position, crown diameter, species, height)-as 3D vegetation modeling input. It’s also necessary to provide classification, information, detail level, and visualization of vegetation model according to landscape architecture analysis needs. This research results are 3D vegetation models in LoD 1-3 with differents information based on appearance, geometry, semantic, and topology aspects of CityGML. Models then tested qualitatively based on visualization and sun shadow analysis. For visualization, the used data only able to generate LoD 1 and 2 vegetation model and the minimum LoD required for sun shadow analysis is LoD 2. Terrestrial data, which provide the real form and size of each tree part, is needed to generate LoD 3 vegetation model.